KTa1- x- yTixGeyO3-δ: A High κ Relaxor Dielectric and Superior Oxide-Ion Electrolyte for IT-SOFC - Yadav A.; Pyare R.; Goodenough J.B.; Singh P. (My University, 2025)
High κ dielectric/ferroelectric KTaO3 in the perovskite structure is envisaged here as a host lattice to develop a superior oxide-ion electrolyte. The lossy nature of high κ relaxor dielectricity in KTa0.4Ti0.3Ge0.3O2.7 was found to result in superior oxide-ion conductivity (σo) at elevated temperatures (σo > 10-2 s/cm, T ≥ 550 °C). The maximum of the dielectric constant was found to be ∼5300 at an applied frequency of 20 kHz at 650 °C, and Tm was decreasing with an increasing applied frequency. The high σo of KTa0.4Ti0.3Ge0.3O2.7 was observed in coherence of Tm variation with applied frequency, thus establishing the role of dielectricity/polarization in accelerating the transport of oxide-ion vacancies within the percolation limit inside the host structure. © 2020 American Chemical Society.